TECHNOLOGIES OF ARTIFICIAL INTELLIGENCE AS THE FACTOR OF DIGITALIZATION OF ECONOMY IN RUSSIA AND IN THE WORLD - L. A. Tsvetkova (Ekonomika Nauki)
The growth rates of the market for high-tech goods and services based on deep learning technologies are estimated. Key investors and beneficiaries in the development of deep learning technologies were identified. The patent activity in the world is analyzed and the place of Russia in the patent landscape in the field of deep learning is determined. It is shown that most of the patent documents are concentrated in the portfolios of major US corporations, which are headed by Microsoft, IBM, Google, Yahoo. Among the leaders of the rating of patent holders are also the corporations of Japan and the Republic of Korea. High rates of growth of patent activity in China are noted. The prospects of the development of artificial intelligence technologies and deep learning in Russia are estimated. Special attention is paid to the fact that most of the research and development in this area is carried out in public research institutes and universities, while in the countries – technological leaders the driver of development of the direction is the business sector.